Circulating liver-specific microRNAs as noninvasive diagnostic biomarkers of hepatic diseases in human. (17th February 2019) - Musaddaq, Ghulam; Shahzad, Naveed; Ashraf, Muhammad Adnan; Arshad, Muhammad Imran
Abstract: Context: Hepatitis is an endemic disease worldwide leading to chronic and debilitating cancers. The viral agents and hepatotoxic substances lead to damage of hepatocytes and release of damage associated molecules in circulation. The lack of timely and rapid diagnosis of hepatitis results in chronic disease. Objective: The present review aimed to describe regulation, release and functions of microRNAs (miR) during human liver pathology and insights into their promising use as noninvasive biomarkers of hepatitis. Methods: Comprehensive data were collected from PubMed, ScienceDirect and the Web of Science databases utilizing the keywords "biomarkers", "microRNAs" and "hepatic diseases". Results: The miRs are readily released in the body fluids and blood during HBV/HCV associated hepatitis as well as metabolic, alcoholic, drug induced and autoimmune hepatitis. The liver-specific microRNAs including miR-122, miR-130, miR-183, miR-196, miR-209 and miR-96 are potential indicators of liver injury (mainly via apoptosis, necrosis and necroptosis) or hepatitis with their varied expression during acute/fulminant, chronic, liver fibrosis/cirrhosis and hepato-cellular carcinoma. Conclusions: The liver-specific miRs can be used as rapid and noninvasive biomarkers of hepatitis to discern different stages of hepatitis. Blocking or stimulating pathways associated with miR regulation in liver could unveil novel therapeutic strategies in the management of liver diseases. Clinical significance: Liver specific microRNAs interact with cellular proteins and signaling molecules to regulate the expression of various genes controlling biological processes. The circulatory level of liver specific microRNAs is indicator of severity of HBV and HCV infections as well as prognostic and therapeutic candidates. The expression of liver specific microRNAs is strongly associated with infectious, drug-induced, hepatotoxic, nonalcoholic steatohepatitis and nonalcoholic fatty liver diseases.